Kilowatt-class planar four-way gysel combiner with power-aware impedance optimization for L-band pulsed radar - Mohamed Mowafy; Mahmoud A. Shawky; Syed Tariq Shah; Abdelhamid A. Shaalan; Safaa Ibrahim; Mai F. Ahmed (PLoS ONE, 2026)
This work presents a compact planar four-way Gysel power divider/combiner designed for kilowatt-class coherent power combining in L-band pulsed radar transmitters. Unlike previously reported waveguide and coaxial Gysel architectures, the proposed planar implementation achieves a 3 kW peak output on an RO4003C substrate while maintaining low-loss, highly manufacturable microstrip construction. A power-aware full-wave electromagnetic optimization framework is introduced to refine characteristic impedances and electrical lengths, explicitly accounting for current distribution, thermal dissipation, and fabrication tolerance sensitivity, resulting in improved mid-band isolation and stable high-power performance. The fabricated prototype achieves an input return loss better than 15 dB, inter-port isolation exceeding 25 dB, amplitude imbalance within ± 0.3 d B , and phase deviation within ± 1 ∘ across 1.2–1.4 GHz. Grounded isolation branches equipped with flange-mounted high-power resistors, together with thermally optimized via arrays, ensure efficient dissipation of odd-mode energy under mismatch conditions. Experimental validation shows close agreement with simulation results, demonstrating that the proposed design represents a rare example of a planar microstrip Gysel combiner experimentally validated for reliable kilowatt-class operation in L-band solid-state radar systems, achieving a practical balance between power handling, compactness, and manufacturability.